2013
DOI: 10.2147/ndt.s49454
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of pramipexole for the treatment of primary restless leg syndrome: a meta-analysis of randomized placebo-controlled trials

Abstract: Primary restless leg syndrome (RLS) is a common sensory-motor disorder that is characterized by an irresistible urge to move the limbs and unpleasant sensations in the legs, which affects 1.9%–4.6% adults. Pramipexole, a potent dopamine D2/3 agonist, is recommended as “effective” in the short-term and “possibly effective” in the long-term treatment of primary RLS in the European guidelines on management of RLS. In this meta-analysis, we summarized the efficacy and tolerability of pramipexole in treatment for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Our case is more consistent with previous reports of toxicity or less common adverse effects with therapeutic use, wherein the major features of toxicity are hallucinations, agitation, psychosis and extrapyramidal effects [5,12,13]. For example, hallucinations appear to be dose-related, being more common in patients treated with larger doses (1.5-4.5 mg daily) of pramipexole for Parkinson's disease, compared to smaller doses (0.125-0.75 mg before sleep) in restless legs syndrome [6,18]. Although these neuropsychiatric manifestations may not be life-threatening, they are difficult to manage and usually require sedation and longer lengths of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Our case is more consistent with previous reports of toxicity or less common adverse effects with therapeutic use, wherein the major features of toxicity are hallucinations, agitation, psychosis and extrapyramidal effects [5,12,13]. For example, hallucinations appear to be dose-related, being more common in patients treated with larger doses (1.5-4.5 mg daily) of pramipexole for Parkinson's disease, compared to smaller doses (0.125-0.75 mg before sleep) in restless legs syndrome [6,18]. Although these neuropsychiatric manifestations may not be life-threatening, they are difficult to manage and usually require sedation and longer lengths of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the study conducted by Zhang et al, 32 the present study included a greater number of existing trials, rated the quality of evidence for all endpoints according to GRADE, performed a sensitivity analysis, conducted publication bias identification and source analysis of heterogeneity. In addition, this study confirmed the efficacy of pramipexole from various perspectives, such as the proportion of patients with an IRLS score reduction of at least 50% after treatment, CGI-I, PGI, and the change in quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…20–31 In addition, the results from different clinical trials are not completely consistent. 20–31 To date, only one systematic review has specifically evaluated the efficacy of pramipexole; 32 however, this review included only six trials 2226,29 and evaluated only two endpoints, and the quality of evidence was not classified according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Moreover, two relevant clinical trials were published at the beginning of 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines recommend dopaminergic agonists (pramipexole, ropinirole, and rotigotine patch) and α‐2‐δ ligands (gabapentin enacarbil and pregabalin) as first‐line pharmacological treatment options for primary RLS. The effectiveness of dopaminergic agonists was confirmed by substantial evidence‐based studies . Nevertheless, the use of dopaminergic agonists was associated with a high risk of augmentation (defined as iatrogenic worsening of symptom severity), limiting their effectiveness in long‐term treatment.…”
mentioning
confidence: 98%
“…The effectiveness of dopaminergic agonists was confirmed by substantial evidence-based studies. [6][7][8][9] Nevertheless, the use of dopaminergic agonists was associated with a high risk of augmentation (defined as iatrogenic worsening of symptom severity), limiting their effectiveness in long-term treatment. Recently, α-2-δ ligands have been considered as another treatment option to relieve RLS symptoms because the augmentation rate associated with α-2-δ ligand treatment is lower than that with dopaminergic agonists.…”
mentioning
confidence: 99%